Yes‐associated protein expression in germ cells is dispensable for spermatogenesis in mice. Issue 10 (6th August 2019) - Abou Nader, Nour; Levasseur, Adrien; Zhang, Xiangfan; Boerboom, Derek; Nagano, Makoto C.; Boyer, Alexandre
Summary: Yes‐associated protein (YAP), a key effector of the Hippo signaling pathway, is expressed in the nucleus of spermatogonia in mice, suggesting a potential role in spermatogenesis. Here, we report the generation of a conditional knockout mouse model ( Yap flox/flox ; Ddx4 cre/+ ) that specifically inactivates Yap in the germ cells. The inactivation of Yap in spermatogonia was found to be highly efficient in this model. The loss of Yap in the germ cells had no observable effect on spermatogenesis in vivo. Histological examination of the testes showed no structural differences between mutant animals and age‐matched Yap flox/flox controls, nor was any differences detected in gonadosomatic index, expression of germ cell markers or sperm counts. Cluster‐forming assay using undifferentiated spermatogonia, including spermatogonial stem cells (SSCs), also showed that YAP is dispensable for SSC cluster formation in vitro. However, an increase in the expression of spermatogenesis and oogenesis basic helix–loop–helix 1 ( Sohlh1 ) and neurogenin 3 ( Ngn3 ) was observed in clusters derived from Yap flox/flox ; Ddx4 cre/+ animals. Taken together, these results suggest that YAP fine‐tunes the expression of genes associated with spermatogonial fate commitment, but that its loss is not sufficient to alter spermatogenesis in vivo.